Improvement in parameters of quality of life and uterine volume reduction after uterine fibroid embolization - Silva,Nathalia Almeida Cardoso da (2020)
ABSTRACT Objective To evaluate improvement in quality of life, reduction of uterine volume, and the correlation between these two variables after uterine fibroid embolization. Methods Data on quality of life before and after uterine fibroid embolization were collected from 60 patients using the Uterine Fibroid Symptom – Quality of Life questionnaire. In 40 of these patients, uterine volume information on magnetic resonance imaging examinations performed before and after uterine fibroid embolization was collected, and compared using the nonparametric Wilcoxon test for paired data. Correlation between quality of life and uterine volume before and after procedure was measured using Spearman’s correlation coefficient. Results There was significant improvement in quality of life after uterine fibroid embolization on Uterine Fibroid Symptom – Quality of Life questionnaire, in both subscales scores and the total score. There was a significant median reduction of -37.4% after uterine fibroid embolization, but no correlations between uterine volume and quality of life scores were found before or after embolization. Conclusion Uterine embolization is an alternative to treat uterine fibroids, resulting in relief of symptoms and better quality of life. Although reduction in uterine volume plays an important role in the evaluation of therapeutic success, it does not necessarily have a definitive correlation with relief of symptoms.